Pembelajaran Qowaid dengan Metode Ulul Albab - Erlina Rahma P; Hibatin Wafiroh; Immaa Iyyaanal F; Orin Saga; Moh Sholeh Afyuddin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This study aims to find out and explain about qowaid learning using the Ulul Albab method. In this study, the research method used was a descriptive qualitative method, while the data collection technique used observation, interviews, questionnaires, and documentation. The research took a discussion about learning qowaid science because of the importance of this science in learning Arabic, especially to make it easier for someone to be able to read the yellow book and other Arabic essays, so that several quick methods of reading the yellow book were created that were applied in various educational institutions, one of which was the Ulul Albab method used at the Ulul Albab Islamic boarding school in Kediri City, This method has books that take references from several Nahwu and Shoroof books. So that the guidance between methods and books in the Ulul Albab method is considered effective and can make it easier for students to learn qowaid knowledge